ORDERING GENDER: REVISITING THE ROLE OF PSYCHOLOGY - Shefer, Tamara (PINS-Psychology in Society, 2026)
Psychology as a discipline has long been criticised for its reproduction of gender and other inequalities. Such a critique has been lodged both at the content of psychological knowledges as well as the practices of psychology, including the realm of academia, intervention and organisational structures. In South Africa it has been well illustrated that white males have dominated in psychology as a practice and in the production of knowledge, particularly in terms of authorship, where black and women psychologists have been under-represented. It has also been widely acknowledged that psychology, in particular the psychology of gender, has been highly problematic in the way in which it reproduces and legitimates gender difference and inequality. While debates about the sexist content of psychological knowledge have been present for a number of decades in the international context, there has been little focus on this in South Africa. the need to develop a South African psychology of gender that is both local - that is, representing indigenous experiences of gender development and identities - and critical - in that it problematises the construction of gender difference and inequality - is another challenge within the broader transformation of South African psychology. This paper revisits criticisms of the way in which psychology has theorised gender difference and presents contesting current perspectives on gender within postmodern thinking, in an attempt to take forward these debates in the reconstruction of South African psychology.